Examining Development Impact Measurement: A case of South African Impact Investors - Bennett, Erin Elizabeth (Graduate School of Business (GSB), 2019)
Over the past decade impact investing has gained much traction as a lucrative category of investments that strive for positive social and environmental impact alongside financial gains. Measurement of the intended impacts is gaining importance as this field of investing grows, requiring increased focus on non-financial performance of investment portfolios by impact investors. Improved measurement practises allow impact investors to not only understand and manage the social and environmental impacts effected through conscious intentions, but also provides an opportunity to proliferate existing positive impact. This report provides empirical insight into the impact measurement techniques employed by South African public and private institutional impact investors, using data collected through over 20 semi-structured research interviews, as well as publicly available impact measurement methodologies. In addition, it contributes to a limited collection of impact data and research that is critical in evidencing the most effective impact investments. Growing this area of research aids in the decision-making of development finance capital allocation to the most impactful investments – particularly those significantly contributing to achievement of the Sustainable Development Goals (SDGs) and the National Development Plan (NDP). A single case-study method was employed in analysing the empirical findings of the primary data sample, with South Africa as the case analysed. The general inductive approach was applied in the analysis of primary and secondary data collected. Categorisations of the data were made using the code-to-theory model. Furthermore, the logic model was employed as a theoretical lens to study the context of the measurement frameworks utilised by participants. The study also investigates the level of transparency in measurement and reporting within South Africa’s growing impact investing industry, for knowledge-sharing and recognition of positive impact. The findings demonstrate that South African impact investors are less inclined to use internationally recognised impact measurement tools such as IRIS and GIIRS rating systems. They currently utilise customised metrics and indicators as well as ESG risk and opportunity identification in measuring and tracking their impact. It also provides evidence of the influence of funders in driving the impact objectives and measurement practises employed by impact investors. The findings further show that there is greater focus on the shorter-term outputs and outcomes of investments, and less consideration of long-term sustainable impact. Recommendations made to South African impact investors include clearly articulating impact goals through application of the theory of change and logic model frameworks, as well as selecting measurement metrics that align closely to the intended short, medium and long-term impact objectives.